Professional Skills Management (PSM) tool benefits for Finnish industrial company - Säntti, Sami Jaakko (My University, 2024)
Resource skill and competence management are important for every company. Competence and the level of competences can be measured in many ways. The resource-based view (RBV) has long since developed and has been one of the most successful theoretical approaches in the field of strategic management. This study has used the perspective provided by the RBV theory and the results have also been compared to previous studies on competence development and competence management. The research was conducted as a case study for a Finnish industrial company and its Energy field service department. The purpose of the work was to find out the knowledge management tools they use globally from the end user's point of view, and to list the most important development items based on the data collected from the users. Data collection was carried out with questionnaires and interviews. When conducting surveys and interviews, the challenges and effects of multiculturalism were considered. At the beginning of the study, two research questions were defined: 1. What are the most common problems in managing skills and competences with the PSM tool? and 2. What are the most specific aspects of the PSM tool that are useful and should be developed? The re-search was done by analyzing the data collected through questionnaires and interviews. The analysis was performed by comparing the results with previous studies and the RVB theory presented in the literature review. In addition, the answers to the questionnaires were checked and the answers were deepened by interviewing all the respondents separately. By using the triangulation method in connection with the comparison, the reliability of the re-search results was ensured. Suggestions for improvement focus on the usability of the PSM tool, the support system, and the quality and availability of the training material. With the chosen research methods, the survey answers to the research questions have been solved within the pre-set limits. The results are still used in the development of the PSM system. The study was the first PSM conducted on the subject for the company and lays the foundation for possible further studies on the subject.

Resurssiosaaminen ja osaamisen hallinta ovat tärkeitä jokaiselle yritykselle. Osaamista ja osaamisen tasoa voidaan mitata monella tapaa. Resurssipohjainen näkemys (RBV) kehittyi kauan sitten ja on ollut yksi menestyneimmistä teoreettisista lähestymistavoista strategisen johtamisen alalla. Tässä tutkimuksessa on käytetty RBV-teorian tarjoamaa näkökulmaa ja tuloksia on myös verrattu aikaisempiin osaamisen kehittämistä ja osaamisen johtamista koskeviin tutkimuksiin. Tutkimus tehtiin tapaustutkimuksena suomalaiselle teollisuusyritykselle ja sen Energia sektorin kenttäpalveluosastolle. Tutkimuksen tarkoituksena oli selvittää heidän globaalisti käyttämiään osaamisen hallintatyökaluja loppukäyttäjän näkökulmasta ja listata tärkeimmät kehityskohteet käyttäjiltä kerätyn tiedon perusteella. Tiedonkeruu toteutettiin kyselylomakkeilla ja haastatteluilla. Kyselyjä ja haastatteluja tehtäessä pohdittiin monikulttuurisuuden haasteita ja vaikutuksia. Tutkimuksen alussa määriteltiin kaksi tutkimuskysymystä: 1. Mitkä ovat yleisimmät ongelmat taitojen ja osaamisen hallinnassa PSM-työkalulla? ja 2. Mitkä ovat PSM-työkalun erityisimmät osa-alueet, jotka ovat hyödyllisiä ja joita pitäisi kehittää? Kerätyn tiedon analyysi suoritettiin vertaamalla tuloksia aikaisempiin tutkimuksiin ja kirjallisuuskatsauksessa esitettyyn RVB-teoriaan. Lisäksi kyselylomakkeiden vastaukset tarkistettiin ja vastauksia syvennettiin haastattelemalla kaikkia vastaajia erikseen. Käyttämällä vertailun yhteydessä triangulaatiomenetelmää tutkimustulosten luotettavuus varmistettiin. Parannusehdotukset keskittyvät PSM-työkalun käytettävyyteen, tukijärjestelmään sekä koulutusmateriaalin laatuun ja saatavuuteen. Valituilla tutkimusmenetelmillä löydettiin vastaukset asetettuihin tutkimuskysymyksiin ennalta asetetuissa rajoissa. Tuloksia hyödynnetään edelleen PSM-järjestelmän kehittämisessä. Tutkimus oli tapus yritykselle ensimmänen PSM aiheesta tehty ja luo pohjan mahdollisille jatkotutkimuksille aiheesta.
Keywords: development (active); knowledge management; professional skills; skills; competence; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management